The Impact of Emotional Leadership on Subordinates' Job Performance: Mediation of Positive Emotions and Moderation of Susceptibility to Positive Emotions - Wan, Jin; Pan, Kun ting; Peng, Yuan; Meng, Ling qiang (Frontiers in Psychology, 2022)
Employees' emotions have an important effect on their job performance, thus leaders can influence subordinates' emotions through emotional contagion and emotional appeal, and ultimately affects their job performance. Based on affective events theory, this study examines the impact of emotional leadership on subordinates' job performance and the mediating role of subordinates' positive emotions, and the moderating role of susceptibility to positive emotion. Hierarchical regression analysis of 362 valid questionnaires showed that: (1) emotional leadership has a significant positive effect on subordinates' job performance; (2)subordinates' positive emotion partially mediated the relationship between emotional leadership and subordinates' job performance; (3) subordinates' susceptibility to positive emotion positively moderated the relationship between emotional leadership and positive emotions, i.e., the higher subordinates' susceptibility to positive emotion, the greater the effect of emotional leadership on their positive emotions. This study validates affective events theory, deepens the understanding of the influence mechanism and boundary conditions of emotional leadership on subordinates' job performance, and provides some references for employee performance management.